Synthesis and Study Medical Application of Nanocomposites Based on grafted Chitosan /Polyvinyl alcohol - Ruwaidah S.Saeed; Widad Abed Shlaka; El-Sayed Negim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In the present study, synthesis of bis Schiff base [I, II] by reaction of one mole of terephthalaldehyde with two mole of 2-amino-5-mercapto-1,3,4-thiadiazole or 4-amino benzene thiol in the ethanol absolute, then compounds [I,II]  were reacted with Na2CO3 of distilled H2O, then chloroacetic acid was added to yield compounds [III,IV]. O-chitosan derivatives [V,VI] were synthesized by reaction of chitosan with compounds [III,IV] in acidic media in distilled water according to the steps of Fischer. O–chitosan (grafted chitosan) [V,VI] was blended with synthetic polymer polyvinyl alcohol (PVA) to produce polymers [VII,VIII], then these polymers were blended with nano: Gold or Silver by using a hotplate stirrer for 3 hours to produce nanocomposites [IX- XII]. The synthesized polymers were identified using spectral analysis techniques, including FTIR,1H-NMR, and scanning electron microscope (SEM). Molecular docking was studied, where operations are used to predict the binding status of compounds with the enzyme and to calculate the free energy (ΔG) of the prepared compounds. Finally, the study of biological activities was screened via two types of bacteria. Also, the anti-cancer activity against human lung adenocarcinoma cells (A549) was studied and compared with standard cell line [REF(R7540) Rat Embryonic Fibroblasts] of some of the blended polymers and nanocomposites, then the acute toxicity test of some nanocomposites was performed.